Controlling Unpleasant Thoughts: Adjustments of Cognitive Control Based on Previous-Trial Load in a Working Memory Task - Pacheco, Luiza Bonfim; Figueira, Jéssica S.; Pereira, Mirtes G.; Oliveira, Leticia; David, Isabel A. (Frontiers in Human Neuroscience, 2020)
Dynamic cognitive control adjustments are important for integrating thoughts and actions that take place during dynamic changes of environmental demands and support goal-directed behavior. We investigated, in a working memory (WM) paradigm, whether dynamic adjustments in cognitive control based on previous trial load influences the neural response to neutral or unpleasant distracters. We also investigated whether individual self-reported abilities in controlling thoughts influences this effect. Participants performed a WM change detection task with low or high working memory-related cognitive demands. An unpleasant or a neutral distractive image was presented at the beginning of each trial, prior to the WM task. We tested for control adjustments that were associated with the load level of the preceding trial task (N-1) on the neural response to the subsequent distractive image. We found an effect of the prior WM task load on a parieto-occipital waveform event-related potential that appeared between 200 and 300ms after the neutral distracter onset. This effect was not observed for the unpleasant distracter. Individual ability for controlling thoughts may influence the effect of cognitive control adjustments on distracter processing during the unpleasant condition. These findings provide evidence that (1) dynamic cognitive control adjustments are impaired by unpleasant distracters and (2) the ability to control unpleasant thoughts is linked to individual differences in flexible cognitive control adjustments and shielding of WM representations from unpleasant distracters.